Quercetin (3,3’,4’,5,7-pentahidroksiflavon)’in Bakır (II) ve Çinko (II) komplekslerin kararlılık sabitlerinin tayini - Ergüzel, Emre Tuğrul (My University, 2006)
QUERCETİN (3,3’,4’,5,7-PENTAHİDROKSİFLAVON)’İN BAKIR(II) VE ÇİNKO(II) KOMPLEKSLERİN KARARLILIK SABİTLERİNİN TAYİNİ Günümüzde çeşitli bitki çaylarının içerisinde bulunan quercetin; biyokimya, gıda kimyası, boya kimyası, tıp kimyası, boya endüstrisi ve kozmetik alanlarında kullanılmaktadır. Genellikle birçok bitkinin kök, gövde ve çiçeklerinde farklı flavonoidlerle birlikte bulunur. Bu çalışmada, quercetinin mordan metalleri olarak bilinen bakır(II) ve çinko(II) ile oluşturduğu komplekslerin kararlılık sabitleri Calvin-Bjerrum ve Irwing-Rossotti yöntemleri kullanılarak potansiyometrik yoldan tayin edildi. Quercetinin dissosiyasyon sabitleri potansiyometrik yöntemle logK1 = 9,70, logK2 = 8,35 olarak bulundu. Yine potansiyometrik olarak Irwing-Rossotti metoduyla oluşum sabitleri ise I = 0.00418’de bakır(II) için = 0,5 için logK1 = 13,95 ,çinko(II) için = 0,5 için logK1 = 7,92 , = 1,5 için logK2 = 3,76 olarak bulundu. Oluşan komplekslerin koşullu oluşum sabitleri hesaplandı ve buradan kompleksleşmenin ortaya çıktığı pH aralıkları bulundu. Bakır(II) ve çinko(II) komplekslerinin bileşimleri ligand/ metal = 2/ 1 olarak bulundu ve bunların yapıları tartışıldı. 2.

RESOLUTION OF BOVINE PLASMA VITAMIN K DEPENDENT PROTEINS BY TWO DIMENSIONAL GEL ELECTROPHORESIS Prothrombin, factor VII, factor IX, factor X, protein C, protein S and protein Z are well-known vitamin K dependent (Gla proteins) proteins which have been purified systematically by time consuming chromatographic methods. It may be useful in clinical practice/ research to perform a less time consuming procedure for simultaneous isolation/ quantification of Gla proteins from plasma. The purpose of this study is to resolve the Gla proteins by two-dimensional (2-D) gel electrophoresis. Gla proteins isolated from normal bovine plasma by barium citrate adsorption and ammonium sulfate elution was subjected to 2-D gel electrophoresis. It was carried out with a pH gradient in the first dimension and by sodium dodecyl sulfate-polyacrylamide gel electrophoresis in the second dimension. More than 8 protein spots were visualized by staining with Coomassie Blue R-250. The number of protein spots was more than the number of well-known plasma Gla proteins. Some of them might be contamination of plasma proteins or degradation products. 2-D method can be used for resolution of human plasma Gla proteins. Further mass spectrophotometric evaluation of the 2-D pattern will be providing useful data for research/ clinical studies. Computer assisted densitometry of the human protein pattern of 2-D may be helpful in clinical studies for simultaneous quantification of plasma Gla proteins.
Keywords: Analitik Kimya; Kimya